Manusia Baru dalam Kolose 3:10: Sebuah Studi Biblis tentang Transformasi Hidup Kristen - Samuel Prasetyo Dara; Didit Yuliantono Adi (STT Pantekosta Jakarta, 2025)
Human life in the present age is inseparably bound to the power of sin that permeates thoughts and actions, including those of believers. Christians are not immune to sin, whether influenced by external factors such as cultural and social environments or by internal inclinations within themselves. Colossians 3:10 presents the concept of “putting on the new self” as both a theological and practical guideline for the life of faith. The Epistle to the Colossians was written by the Apostle Paul to address doctrinal and ethical challenges within the congregation, aiming to reaffirm their new identity in Christ. This study seeks to elaborate four key principles of the new self in Colossians 3:10 and to explore their relevance for contemporary Christian life. Employing a descriptive-theological approach, this research demonstrates that the transformation of believers’ lives is characterized by the renewal of the mind, the establishment of a new identity, conformity to the image of the Creator, and ethical application in daily living. The findings contribute to a deeper theological understanding of Christian spirituality and provide practical implications for nurturing faith amid today’s moral and cultural challenges. Abstrak Kehidupan manusia masa kini tidak terlepas dari kuasa dosa yang merasuk dalam pola pikir dan tindakan, termasuk di dalam diri orang percaya. Orang Kristen tidak kebal terhadap dosa, baik karena faktor eksternal seperti pengaruh lingkungan maupun faktor internal yang muncul dari kecenderungan diri sendiri. Surat Kolose 3:10 menampilkan konsep “mengenakan manusia baru” sebagai pedoman teologis dan praktis bagi orang percaya. Surat ini ditulis Rasul Paulus kepada jemaat Kolose yang menghadapi persoalan doktrinal dan etis, dengan tujuan meneguhkan identitas baru dalam Kristus. Penelitian ini bertujuan menguraikan empat prinsip utama mengenai manusia baru dalam Kolose 3:10 serta relevansinya bagi kehidupan Kristen kontemporer. Dengan menggunakan pendekatan deskriptif-teologis, penelitian ini menegaskan bahwa transformasi hidup orang percaya ditandai oleh pembaruan pemikiran, pembentukan identitas baru, kesesuaian dengan gambar Sang Pencipta, serta penerapan etis dalam kehidupan sehari-hari. Hasil kajian ini berkontribusi pada pemahaman teologis mengenai spiritualitas Kristen dan memberikan implikasi praktis bagi pembinaan iman di tengah tantangan moral dan budaya masa kini. Kata Kunci: Kolose 3:10, Manusia Baru, Orang Percaya